Christianity in Malawi : a source book - Ross, Kenneth R. (Mzuni books, 2020)
Many scholars have noted the importance of Christianity in Malawi and have written on the social, economic and political influence of the Christian faith. What is harder to find is a study of the nature of the faith, and an analysis of the inner logic of the religious consciousness which developed in Malawi as its peoples responded to the Christian message. By bringing forward a selection of key primary sources this book provides the opportunity to read the story of Malawian Christianity "from the inside." It allows some Malawian Christians to speak for themselves so that church history might be formed by listening directly and critically to voices from the past. This revised and expanded edition includes all the primary texts that appeared in the original 1996 version as well as six additional documents that extend the range of the collection.